Peran PT. Syncore Indonesia Dalam Mengembangkan Bumdes (Studi Kasus pada BUMDes Danareja Mandiri) - I Kadek Wirawan; I Gusti Ayu Athina Wulandari; A.A. Sri Purnami (Warmadewa Economic Development Journal (WEDJ), 2023)
Village-Owned Enterprises (BUMDes) are a special concern of the government to encourage the acceleration of rural social and economic development. The establishment of BUMDes in Indonesia is regulated in Law Number 32 of 2004 concerning Local Government in terms of developing BUMDes PT. Syncore Indonesia has a very important role with the creation of this Bumdes.id can grow, strengthen and be able to develop BUMDes throughout Indonesia.